Hypoxic culture conditions induce increased metabolic rate and collagen gene expression in ACL‐derived cells. Issue 6 (16th December 2015) - Kowalski, Tomasz J.; Leong, Natalie L.; Dar, Ayelet; Wu, Ling; Kabir, Nima; Khan, Adam Z.; Eliasberg, Claire D.; Pedron, Andrew; Karayan, Ashant; Lee, Siyoung; Di Pauli von Treuheim, Theodor; Jiacheng, Jin; et al.
ABSTRACT: There has been substantial effort directed toward the application of bone marrow and adipose‐derived mesenchymal stromal cells (MSCs) in the regeneration of musculoskeletal tissue. Recently, resident tissue‐specific stem cells have been described in a variety of mesenchymal structures including ligament, tendon, muscle, cartilage, and bone. In the current study, we systematically characterize three novel anterior cruciate ligament (ACL)‐derived cell populations with the potential for ligament regeneration: ligament‐forming fibroblasts (LFF: CD146 neg, CD34 neg CD44 pos, CD31 neg, CD45 neg ), ligament perivascular cells (LPC: CD146 pos CD34 neg CD44 pos, CD31 neg, CD45 neg ) and ligament interstitial cells (LIC: CD34 pos CD146 neg, CD44 pos, CD31 neg, CD45 neg )—and describe their proliferative and differentiation potential, collagen gene expression and metabolism in both normoxic and hypoxic environments, and their trophic potential in vitro. All three groups of cells (LIC, LPC, and LFF) isolated from adult human ACL exhibited progenitor cell characteristics with regard to proliferation and differentiation potential in vitro. Culture in low oxygen tension enhanced the collagen I and III gene expression in LICs (by 2.8‐ and 3.3‐fold, respectively) and LFFs (by 3‐ and 3.5‐fold, respectively) and increased oxygen consumption rate and extracellular acidification rate in LICs (by 4‐ and 3.5‐fold, respectively), LFFs (by 5.5‐ and 3‐fold, respectively), LPCs (by 10‐ and 4.5‐fold, respectively) as compared to normal oxygen concentration. In summary, this study demonstrates for the first time the presence of three novel progenitor cell populations in the adult ACL that demonstrate robust proliferative and matrix synthetic capacity; these cells may play a role in local ligament regeneration, and consequently represent a potential cell source for ligament engineering applications. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:985–994, 2016.